Aklimatisasi Planlet Kantong Semar (Nepenthes gracilis Korth.) pada berbagai Campuran Media Tanam Tanah Ultisol - Rio Febrianto; Suwirmen Suwirmen; Syamsuardi Syamsuardi (Universitas Andalas, 2015)
The research about Acclimatization of Pitcher Plant (Nepenthes gracilis Korth.) Planlet on Variety of Mixed Planting Medium Ultisol Soil had been conducted from May to August 2014 in Greenhouse and Plant Physiology Laboratory Department of Biology, Faculty of Natural Sciences, Andalas University. This study aimed to determine the influence of the media composition on the growth of seedlings of Nepenthes gracilis Korth. This study used completely randomized design (CRD) method with 5 treatments and 5 replications. The treatments of planting medium were consisted of A. Ultisol soil (control), B. Ultisol soil : manure : sand (1:1:1), C. Ultisol soil : manure : husk (1:1:1), D. Ultisol soil : manure : sand (2:1:1) and E. Ultisol soil : manure : husk (2:1:1). The results showed that treatment A i.e. ultisol soil (control) was the best growing medium for Nepenthes seedlings growth during acclimatization.